2020
DOI: 10.3390/toxics8030060
|View full text |Cite
|
Sign up to set email alerts
|

Human Biomonitoring of Glyphosate Exposures: State-of-the-Art and Future Research Challenges

Abstract: Glyphosate continues to attract controversial debate following the International Agency for Research on Cancer carcinogenicity classification in 2015. Despite its ubiquitous presence in our environment, there remains a dearth of data on human exposure to both glyphosate and its main biodegradation product aminomethylphosphonic (AMPA). Herein, we reviewed and compared results from 21 studies that use human biomonitoring (HBM) to measure urinary glyphosate and AMPA. Elucidation of the level and range of exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 65 publications
3
41
0
Order By: Relevance
“…A central point in the discussion of the endocrine-disrupting potential of glyphosate and GBHs lies in the issue of the toxicological evaluation of technical pesticides or their commercial formulations ( 3 , 51 ). Currently, standard testing guidelines and regulatory bodies in different countries, including regulatory agencies in the European Union, the United States, and Brazil only require a complete toxicological assessment, including testing of endocrine disruption potential, of active ingredients ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A central point in the discussion of the endocrine-disrupting potential of glyphosate and GBHs lies in the issue of the toxicological evaluation of technical pesticides or their commercial formulations ( 3 , 51 ). Currently, standard testing guidelines and regulatory bodies in different countries, including regulatory agencies in the European Union, the United States, and Brazil only require a complete toxicological assessment, including testing of endocrine disruption potential, of active ingredients ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glyphosate and its main breakdown product aminomethylphosphonic acid (AMPA) have been ubiquitously detected in the environment ( 2 ). Surprisingly, there are limited human biomonitoring data on glyphosate, but the available studies indicate ubiquitous presence of both glyphosate and AMPA on human urinary samples from the general population ( 3 5 ). Also, GBHs contain a number of co-formulants, which can be potentially ingested (e.g., via food or water) concurrently with glyphosate and AMPA ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…EPA’s estimation of children exposure to glyphosate is higher than the maximum level suggested [ 210 , 211 ]. All of the environmental exposure studies at Connolly et al [ 212 ] had mean/median levels that were 2% of the ADI or less, and the maximum concentrations found in these studies were all less than 6%. One study on residential exposures showed median and maximum values that were 49% and 53% of the ADI, respectively, while another study reported a maximum value was 87% of EFSA’s ADI; these studies with the highest percentage compared to the ADI are studies that were outside Europe and involved aerial spraying.…”
Section: Risk Assessment Of Glyphosate Through Environment and Diementioning
confidence: 99%
“…Glyphosate and AMPA were selected as priority substances in the Human Biomonitoring for Europe initiative [ 7 ]. There is insufficient evidence to indicate whether glyphosate is metabolized to AMPA in humans, or whether AMPA present in human samples mainly derives from AMPA residues in cultivated food products [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%